Peran Pemerintah Nagari dalam Mensukseskan Program Unggulan Bupati Satu Nagari Satu Event: Studi Kasus Baluluak Bajarami di Nagari Kumango, Kecamatan Sungai Tarab, Kabupaten Tanah Datar - Fauzia Rahma; Zulfina Adriani; Try Syeftiani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the role of the Village Government in making the Regent's Flagship Program One Village One Event a success through a case study of Baluluak Bajarami in Kumango Village, Sungai Tarab District, Tanah Datar Regency. This study uses Soerjono Soekanto's role theory (2013, cited in Mawarni et al., 2024) with a descriptive qualitative approach. Data were obtained through interviews, observations, and documentation studies, then analyzed through the stages of data reduction, data presentation, and drawing conclusions according to Miles and Huberman. The results show that in the active role aspect, the Village Government acts as a figure and leader who carries out socialization, education, coordination, and controls and monitors each stage of the event. In the participatory role aspect, the contribution of human resources, materials, time, and the level of community participation in the implementation of activities is seen. Meanwhile, the passive role aspect is reflected in the attitude of the Village Government that values ​​​​initiatives, is open to other opinions, and values ​​​​every input for the sustainability of the event. The main supporting factors come from local cultural values, local government support, and community and migrant participation, while inhibiting factors include budget limitations. Therefore, strengthening coordination and sustainability strategies are necessary to ensure the event's optimal impact in the future.